Genome-wide maps of chromatin state in pluripotent and lineage-committed cells - Mikkelsen, Tarjei S. (2007)
We report the application of single molecule-based sequencing technology for high-throughput profiling of histone modifications in mammalian cells. By obtaining over 4 billion bases of sequence from chromatin immunoprecipitated DNA, we generated genome-wide chromatin state maps of mouse embryonic stem cells, neural progenitor cells and embryonic fibroblasts. We find that lysine 4 and lysine 27 tri-methylation effectively discriminate genes that are expressed, poised for expression, or stably repressed, and therefore reflect cell state and lineage potential. Lysine 36 tri-methylation marks primary coding and non-coding transcripts, facilitating gene annotation. Lysine 9 and lysine 20 tri-methylation are detected at satellite, telomeric and active long-terminal repeats, and can spread into proximal unique sequences. Lysine 4 and lysine 9 tri-methylation mark imprinting control regions. Finally, we show that chromatin state can be read in an allele-specific manner by using single nucleotide polymorphisms. This study provides a framework for the application of comprehensive chromatin profiling towards characterization of diverse mammalian cell populations.